Masa Keemasan Dinasti Abbasiyah : Peran Intelektual Dalam Pembentukan Peradaban Islam Global - Amrudin Amrudin; Nur Afifa Maharani; Susmihara Susmihara; Syamzan Syukur (CV. ITTC INDONESIA, 2025)
The golden age of the Abbasid Dynasty from 750 to 1258 CE was a pivotal period in the history of Islamic civilization, during which knowledge, philosophy, medicine, mathematics and astronomy experienced remarkable development. This paper examines the factors that made the Abbasids a global center of learning, the contributions of Muslim scholars to the intellectual heritage of the world, and the causes of intellectual decline during the later period of the dynasty. The findings reveal that the strategic location of Baghdad, the support of the caliphs through institutions such as the Bayt al-Hikmah and the translation movement served as key catalysts for scientific advancement. Muslim scholars not only translated earlier works, but also developed new theories and methodologies that later influenced global scientific progress. The decline of the Abbasids was triggered by internal factors such as weak leadership, political instability, and family conflicts, as well as external pressures including the Crusades and the Mongol invasion. In conclusion, the Abbasid glory emerged from political stability, openness and a strong intellectual spirit, whereas its decline occurred when these foundations weakened